Assessment of Long-Term Sustainable End-Use Energy Demand in Romania - Malla, Sunil (Taylor and Francis, 2019)
Romania is the 10th largest economy in EU-28 and also one of the fastest growing economies in the region. An end-use energy demand model is developed for Romania to assess energy requirement by sector and by end-use for 2015–2050 period. Industry would surpass residential sector as the largest final energy-consuming sector from 2035 onwards. Services sector would exhibit the fastest growth of energy consumption. Despite expected decline in country’s population, demand for electricity would grow in the future driven by increased household income and expanded services sector, which is relatively electricity intensive. Still, Romania’s per capita electricity consumption would be about half of the EU-28 average. At the end-use level, thermal processes in industry, space heating in the residential and services, and road passenger travel in transport sector would be dominant throughout the study period. Improvement of energy efficiency in the heating system exhibits the highest potential of energy saving.